A route towards high‐efficiency silicon heterojunction solar cells. (10th November 2021) - Duan, Weiyuan; Lambertz, Andreas; Bittkau, Karsten; Qiu, Depeng; Qiu, Kaifu; Rau, Uwe; Ding, Kaining
Abstract: In this work, we propose a route to achieve a certified efficiency of up to 24.51% for silicon heterojunction (SHJ) solar cell on a full‐size n‐type M2 monocrystalline‐silicon Cz wafer (total area, 244.53 cm 2 ) by mainly improving the design of the hydrogenated intrinsic amorphous silicon (a‐Si:H) on the rear side of the solar cell and the back reflector. A dense second intrinsic a‐Si:H layer with an optimized thickness can improve the vertical carrier transport, resulting in an improved fill factor ( FF ). In order to reduce the plasmonic absorption at the back reflector, a low‐refractive‐index magnesium fluoride (MgF2 ) is deposited before the Ag layer; this leads to an improved gain of short circuit current density ( J sc ). In total, together with MgF2 double antireflection coating and other fine optimizations during cell fabrication process, ~1% absolute efficiency enhancement is finally obtained. A detailed loss analysis based on Quokka3 simulation is presented to confirm the design principles, which also gives an outlook of how to improve the efficiency further. Abstract : We have proposed a route towards a certified efficiency of 24.51% for silicon heterojunction (SHJ) solar cell on an n‐type M2 monocrystalline‐silicon Cz wafer by mainly improving the hydrogenated intrinsic amorphous silicon (a‐Si:H) on the rear side and optimizing the back reflector. A dense second intrinsic a‐Si:H layer with an optimized thickness can improve the vertical carrier transport. A low‐refractive‐index magnesium fluoride deposited before Ag layer can help reduce the plasmonic absorption at the back reflector.